2021
DOI: 10.1186/s12889-021-12191-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the consumption of chlorine dioxide to prevent and treat COVID-19 in the Peruvian population: a cross-sectional study

Abstract: Background Chlorine dioxide has been promoted as an alternative for the prevention and treatment of COVID-19, especially in Peru, despite the lack of evidence to support its efficacy. This study aimed to evaluate the factors associated with chlorine dioxide consumption in the Peruvian population. Methods Analytical cross-sectional study. An adult Peruvian population was evaluated where chlorine dioxide consumption was divided into two groups accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…As noted by the authors, infodemia through social networks, conferences, chats, or daily conversations, sharing supposedly successful experiences of COVID-19 treatment, could explain the increased antibiotic usage before hospitalization, despite the known infrequent bacterial coinfections [ 20 ]. This is congruent with the persistence, almost 2 years after the beginning of the pandemic, in the discarded use of drugs by regulatory institutions, such as ivermectin or chlorine dioxide [ [37] , [38] , [39] ]. This means cultural and information dissemination aspects must be addressed as public health policies.…”
Section: Discussionsupporting
confidence: 59%
“…As noted by the authors, infodemia through social networks, conferences, chats, or daily conversations, sharing supposedly successful experiences of COVID-19 treatment, could explain the increased antibiotic usage before hospitalization, despite the known infrequent bacterial coinfections [ 20 ]. This is congruent with the persistence, almost 2 years after the beginning of the pandemic, in the discarded use of drugs by regulatory institutions, such as ivermectin or chlorine dioxide [ [37] , [38] , [39] ]. This means cultural and information dissemination aspects must be addressed as public health policies.…”
Section: Discussionsupporting
confidence: 59%
“…Other aspects that would explain the high proportion of home fatalities were self-medication and insufficient oxygen supply. At first, a significant fraction of the population preferred to self-medicate with hydroxychloroquine, azithromycin, ivermectin, and even chlorine dioxide, instead of going to a hospital, died in their homes due to the rapid evolution of the disease [ 40 , 41 , 42 ]. Later, the supply of oxygen proved to be largely insufficient in public health facilities in the interior of the country as they did not have oxygen plants, which led people to decide to manage their family members at home, acquiring oxygen from private providers combined with the exaggerated increase in the cost of this service, so many families could not afford it.…”
Section: Discussionmentioning
confidence: 99%
“…Of 3610 adult Peruvian participants, they found a prevalence of 8% and 16% for the prevention and treatment of COVID-19, respectively, indicating that chlorine dioxide is a substance being used for self-medication in COVID-19. 25 A recent systematic review regarding self-medication practices to prevent or manage COVID-19 found that the most frequently used medications were antibiotics, chloroquine or hydroxychloroquine, vitamins or supplements, ivermectin, and ibuprofen. 15 However, other drugs such as aspirin were also reported by high-quality studies.…”
Section: Drug Safety Of Frequently Used Drugs and Substances For Self...mentioning
confidence: 99%
“…Of 3610 adult Peruvian participants, they found a prevalence of 8% and 16% for the prevention and treatment of COVID-19, respectively, indicating that chlorine dioxide is a substance being used for self-medication in COVID-19. 25 …”
Section: Introductionmentioning
confidence: 99%